Etiologies and posttreatment conditions of thyrotoxic patients in Sylhet division, Bangladesh: A clinical series - Mahmud, Md Kayes; Jalil, Shahnaz; Rahman, AHM Mahmudur; Rashid, Md Mamun Ur; Sultana, Shiny; Taher, Adnan; Haque, Lutful; Fardous, Jannatul; Nahar, Kamrun (Avicenna Journal of Medicine, 2017)
Objective: The endeavor of the study was to analyze the posttreatment (postradioactive iodine therapy [RAI]) conditions of thyrotoxic patients in a tertiary level hospital. Materials and Methods: A retrospective study of 186 patients was conducted from 2012 to 2014 in Institute of Nuclear Medicine and Allied Sciences (INMAS), Sylhet MAG Osmani Medical College Campus. Patients' information regarding the etiologies and their disease status after getting RAI therapy was recorded. Results: In this study, 29.57% patients were male and 70.43% were female where the mean ages were 44.57 and 43.46 accordingly. The most vulnerable group was in between 41 and 50 years of age, which is 25.81%. The patients were categorized according to the etiologies as Graves' disease (GD), multinodular goiter (MNG), and single toxic nodule (STN). In primary stage, 60.22% patients had GD, 26.88% had MNG, and 12.90% had STN. After 6 months of RAI therapy, the disease status of 51.61% patients became euthyroid, 19.35% became hypothyroid, and 29.03% remained thyrotoxic. Thus, a second dose of RAI therapy was given to those patients for next 6 months. After 12 months from the beginning of the therapy of each patient, the total recovery was found to be 72.04%. However, though all the GD patients improved to either euthyroid or hypothyroid state after 6 months, on a 12-month observation, 17.86% of them regained the thyrotoxicosis due to discontinuation of the treatment. Conclusion: The findings show an overall significant recovery of thyrotoxic patients taking RAI therapy in INMAS and important points to improve the rate.
Keywords: Etiology; Graves' disease; multinodular goiter; radioactive iodine therapy; thyrotoxicosis